The Structure and Electrochemical Properties of Laser Irradiation of TiS2 / C Composite - L.S. Yablon; V.V. Strelchuk; I.М. Budzulyak; S.I. Budzulyak; О.V. Morushko; B.I. Rachiy; О.М. Hemiy (Журнал нано- та електронної фізики)
The optical and electrochemical properties of titanium disulfide / nanoporous carbon compo-site are studied for the purpose of its use in the energy storage systems. It is established that laser irradiation of the formed composite increases the specific capacity of the corresponding devices ten times and stabilizes the charge / discharge processes.